3(9y-2.6)+7.2=6(8y-0.1)

Simple and best practice solution for 3(9y-2.6)+7.2=6(8y-0.1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(9y-2.6)+7.2=6(8y-0.1) equation:


Simplifying
3(9y + -2.6) + 7.2 = 6(8y + -0.1)

Reorder the terms:
3(-2.6 + 9y) + 7.2 = 6(8y + -0.1)
(-2.6 * 3 + 9y * 3) + 7.2 = 6(8y + -0.1)
(-7.8 + 27y) + 7.2 = 6(8y + -0.1)

Reorder the terms:
-7.8 + 7.2 + 27y = 6(8y + -0.1)

Combine like terms: -7.8 + 7.2 = -0.6
-0.6 + 27y = 6(8y + -0.1)

Reorder the terms:
-0.6 + 27y = 6(-0.1 + 8y)
-0.6 + 27y = (-0.1 * 6 + 8y * 6)
-0.6 + 27y = (-0.6 + 48y)

Add '0.6' to each side of the equation.
-0.6 + 0.6 + 27y = -0.6 + 0.6 + 48y

Combine like terms: -0.6 + 0.6 = 0.0
0.0 + 27y = -0.6 + 0.6 + 48y
27y = -0.6 + 0.6 + 48y

Combine like terms: -0.6 + 0.6 = 0.0
27y = 0.0 + 48y
27y = 48y

Solving
27y = 48y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-48y' to each side of the equation.
27y + -48y = 48y + -48y

Combine like terms: 27y + -48y = -21y
-21y = 48y + -48y

Combine like terms: 48y + -48y = 0
-21y = 0

Divide each side by '-21'.
y = 0

Simplifying
y = 0

See similar equations:

| -5b^2=-180 | | 3y-2x=.5 | | m=-1/4,b=3/5 | | 3c+2c=-95 | | -1.56-2.6y=2.6(y+8.8) | | 18=3s-10+4s | | 9y-8=7y+8 | | 7(x+2.1)=14x-2.8 | | -5x+16=-8(x+1)+6x | | 11=3c+5 | | -1/8z=-6.5 | | 3y-15=2y-5 | | N+5=8+7 | | -134=6x-6+2x | | (3/4)c=9 | | xy=-9 | | 7b^2=252 | | 2y-15=2y+5 | | 3a-2[4-2(a-5)]=5a-19 | | 6x+4=8x-(-8) | | 7a-9=12(a-5) | | -4q-8+6q=20 | | (8x^4+2x^2-1)+(3x^3-5x^2+7x)= | | 5(x+4)=9x-6 | | (8e).1= | | 4.7+1.2x=2.2x | | 6n-202=4(2-6n) | | 24+3n=1.5 | | 9x^3+3x^2-30x=0 | | 11.7b+5=5.2b+33.60 | | 14+b=2-3b | | F(3)=2x+10 |

Equations solver categories